Hell and other destinations a 21st-century memoir - Albright, Madeleine (New York Harper Collins, 2020)
In 2001, when Madeleine Albright was leaving office as America?s first female secretary of state, interviewers asked her how she wished to be remembered. ?I don?t want to be remembered,? she answered. ?I am still here and have much more I intend to do. As difficult as it might seem, I want every stage of my life to be more exciting than the last.?
Includes index
Keywords: Madeleine Albright